MILITER DALAM DEMOKRASI INDONESIA (PERIODE PEMERINTAHAN JOKO WIDODO) - Immanuel, Glenn Kevin; Djuyandi, Yusa (Jurnal Nawala Politika, 2023)
This research tries to explain the military in the context of democracy in Indonesia during the Joko Widodo government period. The revocation of ABRI's dual function is a form of military withdrawal from the realm of practical politics. Even though the military has withdrawn from practical politics, the military still has political power that has quite an influence on politics in Indonesia. This can be seen from the inclusion of several retired military officers in Joko Widodo and Ma'ruf Amin's campaign team in 2019. Apart from that, many retired military officers held political and non-political positions during Joko Widodo's government. In fact, several active military officers hold several positions in civil institutions and state-owned enterprises. This certainly has an impact on the tarnishing of democracy in Indonesia. This research uses descriptive qualitative research methods with library study data collection methods.